International R&D alliances and innovation for emerging market multinationals: roles of environmental turbulence and knowledge transfer. Issue 6 (1st July 2019) - Liu, Yang; Deng, Ping; Wei, Jiang; Ying, Ying; Tian, Mu
Abstract : Purpose: The purpose of this paper is to examine the relationships between environment turbulence, knowledge transfer and innovation performance for emerging market multinationals (EMNEs) in an asymmetric international R&D alliance. Design/methodology/approach: Data were collected through a survey of high-tech firms in Zhejiang Province of China from 2013 to 2015. Findings: Innovation performance of EMNEs is positively influenced by knowledge transfer activities (knowledge replication and knowledge adaption), technological and market turbulence, while negatively influenced by institutional turbulence. In addition, different aspects of environmental turbulence moderate the relationship between knowledge transfer practices and innovation performance of EMNEs differently. Research limitations/implications: Future studies could use a longitudinal design to capture the dynamism driving innovation performance of EMNEs through R&D alliances. Practical implications: Practical guidelines are provided particularly for EMNE managers on how to develop an innovation strategy by leveraging external knowledge, adaptive innovation and environmental turbulence. Originality/value: This study deepens the knowledge of how EMNEs enhance their innovation by building the linkage between environmental turbulence and absorptive capacity through knowledge transfer activities in an asymmetric international R&D alliance.